TANTANGAN IMPLEMENTASI BANGKOK DECLARATION DALAM MENGATASI MARINE DEBRIS DI FILIPINA TAHUN 2019-2025 - pratiwi, yunita; Alfajri; Rendi Prayuda (TRANSBORDERS: International Relations Journal, 2025)
Marine debris is one of the most pressing environmental challenges in the modern era, with the Philippines as one of the largest contributors. This study explores the challenges in implementing the Bangkok Declaration to address marine debris in the Philippines 2019-2025. This study uses the theory of pluralism, namely the plurality of actors in efforts to prevent and reduce marine debris in the Philippines. Through descriptive qualitative research using literature study data collection techniques, the results of this study indicate that around 80% of marine debris comes from land activities, with plastic as the dominant component. The seriousness of the Philippines in implementing the Bangkok Declaration on Marine Debris can be seen from the involvement of various actors. The actors who play a role in efforts to prevent and reduce marine debris in the Philippines include the government, private sector, NGOs, and also local communities. However, there are still several challenges in implementing the Bangkok Declaration on Marine Debris in the Philippines, including the lack of waste management infrastructure, low public awareness, weak law enforcement and the problem of plastic waste imports. Despite these challenges, the Philippines' opportunity to at least approach the target of reducing marine debris remains open. This can be achieved by increasing investment in waste processing infrastructure, effective education campaigns, strengthening regulations and law enforcement, and increasing international cooperation to address waste problems, all of which must be implemented in a comprehensive, measurable and responsible manner by all actors involved.